A kind of coffee yarn synthetic leather with high added value and production method thereof
By using non-woven fabrics containing coffee staple fibers and hydrolysis-resistant impregnated resins in the production of synthetic leather, and adding wood powder to the coating, the shortcomings of existing synthetic leather in terms of breathability and feel are solved, and a high value-added and environmentally friendly coffee yarn synthetic leather is achieved.
Patent Information
- Application Number
- CN202310464760.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-26
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-04-26
AI Technical Summary
The existing synthetic leather has shortcomings in meeting comfort, fashion and environmental protection requirements, especially in the combination with coffee carbon fiber base cloth, which is difficult to achieve in terms of breathability and feel.
A non-woven fabric containing coffee staple fiber is used as the base, and through the steps of impregnation-containing rolling, pre-solidation, coating and water solidification, combined with hydrolysis-resistant impregnation resin and polyester polyether blend resin, and wood powder is added to increase the bubble cells of the PU coating and improve breathability.
It produces coffee yarn synthetic leather with good feel, high breathability and environmental protection, with high added value and is suitable for textile and clothing, shoes, boots, luggage and other products.
Smart Images

Figure CN116427181B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of synthetic leather, and in particular relates to a high value-added coffee yarn synthetic leather and a production method thereof. Background Art
[0002] Natural leather is widely used in the production of daily necessities and industrial products due to its excellent natural properties. However, as the demand for leather has doubled, the limited amount of natural leather has long been unable to meet people's needs. In order to solve this contradiction, scientists began to study and develop artificial leather and synthetic leather to make up for the shortcomings of natural leather. The earliest synthetic leather used synthetic fiber non-woven fabrics such as polyester and nylon as the base, reinforced with fabric in the middle, and soaked in a polyurethane (PU) solution similar to the composition of natural leather collagen fibers. It solidified in water, and the solvent was replaced by water to form tiny pores, forming a tough and elastic microporous layer from the surface to the inside, which became the surface layer of the synthetic leather and formed a whole with the base.
[0003] At present, synthetic leather is usually made of impregnated non-woven fabric as a mesh layer and microporous polyurethane layer as a grain layer; its front and back sides are very similar to leather, and it has a certain degree of air permeability, which is closer to natural leather than ordinary artificial leather. It can be used in textiles, clothing, shoes, bags, and decorations. Today, as safety and health are increasingly concerned, people have put forward higher requirements for textiles, clothing, and decorative items, which not only meet the new needs of comfort and fashion, but also are closer to the theme of the times of "green, environmental protection, and low carbon". Summary of the invention
[0004] In view of this, the present invention provides a high-value-added coffee yarn synthetic leather and a production method thereof. Through the process method of the present invention, environmentally friendly synthetic leather with good hand feel and breathability can be produced, and the functional added value is high.
[0005] The present invention provides a method for producing high value-added coffee yarn synthetic leather, comprising the following steps:
[0006] The base is a non-woven fabric containing coffee staple fibers;
[0007] The non-woven fabric base is sequentially subjected to impregnation rolling, pre-solidification, coating, and then solidified in water to obtain a semi-finished product; the impregnation material is fluorine-free and uses a hydrolysis-resistant impregnation resin; the coating process uses a polyester-polyether blended resin and adds wood powder;
[0008] The coagulated semi-finished product is washed with water, and then heated and dried to obtain coffee yarn synthetic leather.
[0009] Preferably, the non-woven fabric substrate comprises coffee staple fibers, nylon and recycled polyester; the coffee staple fibers account for 15-20% by mass in the substrate.
[0010] Preferably, the impregnation material is obtained by stirring and mixing a hydrolysis-resistant impregnation resin and a first solvent; and the room temperature viscosity of the impregnation material is controlled at 80-200 cps.
[0011] Preferably, the slurry of the coating is fluorine-free and is obtained by stirring and mixing a polyester-polyether blended resin, wood powder and a second solvent; the mixed slurry is stirred at a stirring speed of 1000-1500 r / min for 30-35 minutes at room temperature.
[0012] Preferably, the weight ratio of the polyester-polyether blended resin to the wood powder in the coating process slurry is 100:1-5, and the room temperature viscosity of the slurry is 10000-12000 cps.
[0013] Preferably, the first solvent and the second solvent are both dimethylformamide; color paste can be optionally added to the slurry of the impregnation material and the coating.
[0014] Preferably, the in-water coagulation adopts a three-layer coagulation method, and the feeding speed is 10-12 m / min.
[0015] Preferably, the thickness of the semi-finished product after solidification is controlled between 1.35-1.40 mm; and the water washing is provided with multiple groups of water washing tanks, wherein the final water washing temperature is controlled at 60-80°C.
[0016] Preferably, the heating and drying comprises: pre-ironing with an ironing roller at 100-120°C, followed by drying at 140-160°C.
[0017] The present invention provides coffee yarn synthetic leather obtained by the production method as described above, with a thickness of 1.1-1.2 mm and / or a softness test value between 1.9-2.5.
[0018] Coffee carbon fiber is generally made of coffee grounds left after drinking coffee, which are calcined to form crystals, then ground into nano powders, added to polyester fibers, and produced into a functional polyester staple fiber. Coffee is one of the daily beverages, and the grounds after making coffee also have some residual value functions, such as absorbing odors, dehumidifying and sweating, and can be recycled. Some companies apply nanotechnology to daily waste coffee grounds, using high temperature and activation, combined with "nanosilver particles" and "water-absorbent polymer compounds" to develop functional fibers (referred to as coffee yarns) with polyester, nylon, viscose, etc. as carriers. Among them, the coffee grounds are calcined at more than 1000 degrees Celsius to make their crystal phases and pores present the best state, and the latest nanotechnology is used for micronization and grinding into 100-300 nanometer powders; secondly, they are processed into masterbatches suitable for fiber production through special processes, and the corresponding spinning and drawing processes are studied to ensure the spinnability of the products in the post-processing plant. Finally, special spinnerets can be designed to solve processing problems that arise in key production processes such as drying, spinning and drawing.
[0019] Coffee yarn has the following functions: 1. Environmental protection: Reduce carbon footprint, its carbon emissions are 48% less than bamboo charcoal and 85% less than coconut charcoal. 2. Antibacterial and deodorizing: The porous adsorption effect of coffee grounds effectively controls the moisture on the body surface, thereby inhibiting the growth of bacteria, and the odor ammonia released when bacteria grow is greatly reduced, so coffee charcoal can also effectively deodorize. 3. Warming and warmth retention: After testing, coffee carbon fiber has a higher temperature rise than ordinary PET fiber under light irradiation, so you can enjoy a natural and warm feeling. Coffee carbon fiber itself has good adsorption and air permeability, and how to better combine it with the PU wet process is the main difficulty of the present invention.
[0020] Compared with the prior art, the present invention adopts a non-woven base fabric containing coffee staple fibers, which is sequentially rolled with an impregnated material, pre-solidified, and coated, and then solidified in water to obtain a semi-finished product, which is then washed, heated, and dried to obtain a coffee yarn synthetic leather; wherein the impregnated material is fluorine-free and uses a hydrolysis-resistant impregnated resin; the coating process uses a polyester polyether blended resin, and adds wood powder. The present invention uses a non-woven fabric containing coffee staple fibers as a base, and selects a fluorine-free resin with a suitable modulus for matching. In the formula, wood powder is added to increase the pores of the PU coating to make it more breathable. The present invention adjusts the machine process, and through the combination of the wet process flow and the coffee carbon fiber base fabric, a synthetic leather with high physical properties such as breathability and good hand feel is developed, and the coffee yarn synthetic leather is environmentally friendly, has high added value, and is easy to use. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 A schematic diagram of a production device flow chart of an embodiment of the present invention;
[0022] Figure 2It is a schematic diagram of the production device flow of the comparative example of the present invention;
[0023] Figure 3 This is a photograph of the pore structure of the synthetic leather produced in Example 1 of the present invention. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0025] The present invention provides a method for producing high value-added coffee yarn synthetic leather, comprising the following steps:
[0026] The base is a non-woven fabric containing coffee staple fibers;
[0027] The non-woven fabric base is sequentially subjected to impregnation rolling, pre-solidification, coating, and then solidified in water to obtain a semi-finished product; the impregnation material is fluorine-free and uses a hydrolysis-resistant impregnation resin; the coating process uses a polyester-polyether blended resin and adds wood powder;
[0028] The coagulated semi-finished product is washed with water, and then heated and dried to obtain coffee yarn synthetic leather.
[0029] By adopting the process method of the invention, environmentally friendly synthetic leather with good hand feel and air permeability can be produced, which has high added value.
[0030] See also Figure 1 , Figure 1 The figure is a schematic diagram of the production device process of an embodiment of the present invention. The embodiment of the present invention uses commercially available coffee yarn staple fibers (mainly purchased from Wokaisi Chemical Fiber Company) as the core part of the synthetic leather base fabric, and produces the non-woven fabric base containing coffee yarn by adding a certain proportion of coffee yarn staple fibers, nylon, and polyester, and then produces synthetic leather with high added value by combining such coffee yarn base fabric with a PU two-step wet process.
[0031] The non-woven fabric base described in the embodiment of the present invention is a non-woven fabric containing coffee staple fibers. Considering the comfort of the hand, a certain proportion of nylon is added to the non-woven fabric. In a preferred embodiment of the present invention, the non-woven fabric base components include coffee staple fibers, nylon and recycled polyester; the commercially available or prepared non-woven fabric of the components can be selected as a synthetic leather base fabric. Preferably, the mass proportion of the coffee staple fibers in the base is 15-20%; the proportion of nylon (nylon) is 25-30%, and the proportion of recycled polyester is preferably 50-55%.
[0032] In addition, the thickness of the non-woven fabric substrate may be 0.7-0.95 mm, and the gram weight (weight per square meter) is generally 200-250 g. In some embodiments of the present application, the thickness of the non-woven fabric substrate is controlled to be 0.7-0.8 mm, and the gram weight (weight per square meter) is 200-220 g, preferably 205-215 g; the burst is 18 kgf / cm 2 , tensile strength warp> 300N / 3CM, weft> 300N / 3CM; elongation at break warp 40-90%, weft 60-120%, preferably elongation at break warp 50-70%, weft 80-100%. In other embodiments, the thickness of the non-woven fabric substrate is 0.85-0.95 mm, the gram weight (weight per square meter) is 225-245 grams, preferably 230-240 grams; the burst is 20kgf / cm 2 , tensile strength in warp direction>350N / 3CM, in weft direction>350N / 3CM; elongation at break in warp direction 40-90%, in weft direction 60-120%, preferably elongation at break in warp direction 50-60%, in weft direction 80-90%.
[0033] In the embodiment of the present invention, the non-woven fabric base is unwound and then rolled with the impregnated material (referred to as impregnation), that is, the square of the non-woven fabric containing coffee staple fibers first passes through the cloth storage rack, and the speed is preferably 10-12m / min, and then passes through the impregnation tank with the impregnated material. Here, the pressure of the impregnated oil pressure roller needs to be controlled, and the pressure can be controlled at 5-5.5Kg. In the selection of impregnated resin, the embodiment of the present invention selects a hydrolysis-resistant impregnated resin, preferably DMI (1,3-dimethyl-2-imidazolidinone) / BDO (1,4-butanediol) polyurethane polyol; and does not contain fluorine compounds. Specifically, its solid content can be 30%, the 100% modulus is 90MPa, the tensile strength is greater than 20MPa, the elongation is ≥300%, and the viscosity range is 100000-120000cps / 25℃. The resin solidifies faster in the DMF solution, and the pores will be larger, so that the air permeability of the impregnated material is better.
[0034] In a preferred embodiment of the present invention, the impregnation material is obtained by stirring and mixing a hydrolysis-resistant impregnation resin and a first solvent; the first solvent is preferably dimethylformamide (DMF). The impregnation material may also include tear-resistant additives, nonionic surfactants, hydrolysis-resistant additives, leveling agents, and color pastes, among which the tear-resistant additives mainly function to increase the bonding strength between non-woven fibers and improve the overall tear strength of finished leather. Commercially available products such as tear-resistant additives XCW-08WH (purchased from Asahikawa Chemical Co., Ltd.) can be used. The nonionic surfactant is preferably S-7 (purchased from Shanghai Riduo Polymer Materials Co., Ltd.), the main components of which are polyether and silicone oil, and do not contain fluoride ions, which has a certain effect on adjusting the pores and feel. The hydrolysis-resistant additive is preferably SI-121 (purchased from Yisan Chemical Co., Ltd.), the main component of which is propylene polycarbonate silicon modified polymer, which can prevent the generation of bubbles when used in the impregnation material and improve the hydrolysis resistance. The main component of the leveling agent is organic silicon, which is added to the impregnated material to improve the dispersion of the color paste and prevent spots, such as the commercially available product HS-1868 (purchased from Minglong Chemical Co., Ltd.). Color paste is a low-toxic pigment with a viscosity of 6000-8000cps / 25℃.
[0035] When the preferred embodiment of the present application is specifically configured, the impregnated resin: dimethylformamide: anti-tear aid: non-ionic surfactant: hydrolysis-resistant aid: leveling agent: color paste are added in a weight ratio of 100: 300-380: 15-17: 0.5-1: 1-2: 1-2: 15-20. This impregnated resin solidifies quickly and the bubbles will be larger. In order to ensure the hand feel, the problem is solved by adjusting the viscosity of the impregnated material. Through different test comparisons of some embodiments, when the number of dimethylformamide added is 300-380 parts, the hardness and softness of the hand feel can meet the requirements. Through test comparisons, when the amount of anti-tear aid added exceeds 18 parts, there will be a risk of sticking. When the anti-tear aid is added in 15-17 parts, the tear strength meets the requirements and there is no risk of sticking. Preferably, the impregnation liquid after the main ingredients are mixed is stirred at a stirring speed of 1000-1500r / min at room temperature for 15-20 minutes until the resin, color paste and hydrolysis resistance additive are completely dissolved, and the room temperature viscosity is controlled at 80-200cps (some embodiments are 80-120cps, preferably 90-110cps, or 140-200cps, preferably 150-170cps).
[0036] After the impregnation is completed, the pre-coagulation liquid tank is passed, and the sugar content can be 30-32% (the sugar content is the DMF concentration in the DMF aqueous solution, measured by the Abbe refractometer, and the following sugar content is obtained from this), and the pressure of the pre-coagulation oil pressure roller is also controlled at 5-5.5Kg. After that, the embodiment of the present invention passes through a six-round ironing device (the ironing temperature can be controlled at 50 degrees Celsius), and finally passes through a coating table device equipped with a coating knife.
[0037] Regarding the selection of polyurethane resin in the coating process, the embodiment of the present invention selects polyester-polyether blended resin, which generally has a high solid content, excellent leather resilience, high peel strength and does not contain fluorine compounds in the resin. Specifically, its solid content is preferably 35-40%, the 100% modulus is 50MPa, the tensile strength is greater than 45MPa, the elongation is ≥500%, and the viscosity range is 160000-180000cps / 25℃. Commercially available resins can be used. This type of resin itself has fine pores and high peel strength. In order to better match the air permeability effect of the base fabric, the present invention mainly adjusts the pores in the coating formula.
[0038] The embodiment of the present invention configures the front coating slurry (which can be referred to as the fabric), wherein the polyester polyether blended resin: dimethylformamide: nonionic surfactant: hydrolysis-resistant additive: color paste are added in a weight ratio of 100:40:0.5-1:0.5-1:1-2, dimethylformamide is a solvent, and other additives can be the same as the impregnated material. The nonionic surfactant is added to the fabric to adjust the uniformity of the overall pores of the coating and improve the washing effect. The hydrolysis-resistant additive is added to the fabric to improve the overall hydrolysis resistance. This formula test shows that the peeling strength is high, the pores are relatively fine, and the air permeability does not meet the expected effect. To solve this problem, wood powder is added as a filler in the above formula to increase the pores. Wood powder has a large specific surface area, a small density, and a low cost. The selected wood powder mesh is preferably controlled at 200-300 meshes; the number of added wood powder should not be too much, otherwise it is easy to cause insufficient peeling strength. After adding different numbers of wood powder, it was finally determined that the addition amount was 1-5 parts, preferably 3 parts, which can meet the requirements.
[0039] Furthermore, in the embodiment of the present invention, the mixed fabric is stirred at a high speed of 1000-1500r / min at room temperature for 30-35 minutes until the polyurethane, filler, color paste, and hydrolysis-resistant additive are completely dissolved. The time of high-speed stirring of the fabric is strictly controlled between 30-35 minutes. If the time is too short, the slurry may not be stirred sufficiently, and if the time is too long, the material temperature will be too high and cause dead material. Stir until the slurry is uniform, reduce the stirring speed to 300±50r / min for vacuum degassing for 90 minutes, and the viscosity can be controlled at 10000cps-12000cps (temperature 32°C), preferably 11000cps. During the coating of the slurry, the thickness of the coating can be controlled by adjusting the scraper gap. The coating gap is controlled between 205±5 silks, and the coating amount is 1.3±0.05kg / y. After unloading, pay attention to the surface condition of the coating and deal with any abnormalities in time.
[0040] After the coating is finished, if the coating is solidified in a single-layer solidification tank, the solidification speed is too fast. Since the addition of wood powder in the formula will make the pores larger and affect the peeling, the present invention preferably adopts a three-layer solidification method for the solidification in water, and the feeding speed is 10-12m / min. In the preferred embodiment of the present invention, the coated surface layer enters a three-fold solidification tank with a length of 30 meters (such as Figure 1 As shown), the slurry is solidified in water for a long time, and water replaces DMF to realize wet coating foaming. The solidification sugar content can be 18-21%, and the temperature is 30±2°C. The embodiment of the present invention solidifies through a three-fold solidification tank, which increases the solidification time of the solidification tank, makes the slurry solidify more fully, and the pores are finer. In this way, the combined treatment of the coating pores, formula and production process is integrated, and the produced product meets both the physical properties and the requirements of the feel.
[0041] When the semi-finished synthetic leather obtained in the embodiment of the present invention comes out of the coagulation tank, the surface condition is observed, and the thickness and width are measured. The thickness is preferably controlled between 1.35-1.40 mm, and the width is between 1.47-1.49 m. Next, it enters multiple groups of washing tanks to wash out the DMFA in the base fabric (BASE); generally, 15 groups of washing tanks are set, and the sugar content of the first six groups of water washing can be controlled at 20-10%, the sugar content of the middle six groups of water washing can be controlled at 10-0%, and the sugar content of the last three groups of water washing is 0%; the water washing temperature of the last three groups is controlled at 70℃±5.
[0042] In a specific embodiment of the present invention, the leather is heated and dried after exiting the water washing tank, preferably including: pre-ironing with eight rounds of ironing rollers (heating rollers) (temperature is 110±10°C); the leather after pre-ironing is dried in an oven, and the oven temperatures are: the first group is 150°C, the second to fourth groups are 160°C, and the fifth group is 140°C, until it is completely dried. In some embodiments of the present invention, the leather can be cooled and rolled after drying, and the thickness of the synthetic leather product is 1.1-1.2mm and the width is 145-147cm.
[0043] The embodiment of the present invention provides coffee yarn synthetic leather obtained by the production method as described above, with a thickness of 1.1-1.2 mm and / or a softness test value between 1.9-2.5.
[0044] According to the above implementation steps, the embodiment of the present invention can make coffee yarn synthetic leather (also called coffee grounds synthetic leather, etc.) in a consistent operation mode. The produced base finished product can reach 120N / 3cm in a three-centimeter peeling test; the softness test value is between 1.9-2.5, the fluorine content meets environmental protection requirements, and has good adsorption and ventilation effects, and also has a certain effect on deodorization.
[0045] In order to better understand the technical content of the present invention, the following specific examples are provided to further illustrate the present invention. In the following examples, two non-woven fabrics of different specifications are selected (both produced by Fujian Nanfang Sanitary Materials Co., Ltd., in which 18% coffee yarn staple fibers purchased from Wokaisi Chemical Fiber, 30% nylon, and 52% recycled polyester are added):
[0046] (1) The thickness of the non-woven fabric is controlled at 0.7-0.8 mm, the gram weight (weight per square meter) is 205-215 grams, and the burst is 18kgf / cm 2 , tensile strength warp> 300N / 3CM, weft> 300N / 3CM, elongation at break warp 50-70%, weft 80-100%; (2) the thickness of the non-woven fabric is 0.85-0.95 mm, the gram weight (weight per square meter) is 230-240 grams. The blasting is 20kgf / cm 2 , tensile strength in warp direction >350N / 3CM, in weft direction >350N / 3CM, elongation at break in warp direction 50-60%, in weft direction 80-90%.
[0047] Hydrolysis-resistant impregnated resin DMI / BDO polyurethane polyol, and does not contain fluorine compounds, with a solid content of 30%, a 100% modulus of 90MPa, a tensile strength of >20MPa, an elongation of ≥300%, and a viscosity of 100000-120000cps / 25℃;
[0048] The polyester-polyether blended resin does not contain fluorine compounds, has a solid content of 35%, a 100% modulus of 50 MPa, a tensile strength of >45 MPa, an elongation of ≥500%, and a viscosity of 160,000-180,000 cps / 25°C.
[0049] The mesh size of wood powder is controlled at 200-300 mesh; the tear-resistant additive XCW-08WH is purchased from Asahikawa Chemical, the non-ionic surfactant S-7 is purchased from Shanghai Riduo Polymer Materials Co., Ltd., the hydrolysis-resistant additive SI-121 is purchased from Yisan Chemical, and the leveling agent HS-1868 is purchased from Minglong Chemical Co., Ltd.; the color paste viscosity range is 6000-8000cps / 25℃, blue.
[0050] Example 1
[0051] (1) Use 0.7-0.8 mm non-woven fabric, first pass through the fabric storage rack, the speed is 10m / min, then pass through the impregnation tank with impregnation material, the pressure of the impregnation oil pressure roller is controlled at 5-5.5Kg. After impregnation, pass through the pre-coagulation liquid, the sugar content is 30-32%, the pressure of the pre-coagulation oil pressure roller is also controlled at 5-5.5Kg, then pass through the six-wheel ironing device (ironing temperature is controlled at 50 degrees Celsius), and finally pass through the coating table device equipped with a coating knife. At the same time, the fabric configured according to the following method is coated on the non-woven fabric along the scraper. The coating gap is controlled between 205±5 silk, and the coating amount is 1.3±0.05kg / y.
[0052] The configuration of the impregnation material includes: hydrolysis-resistant impregnation resin: dimethylformamide: anti-tear additive: non-ionic surfactant: hydrolysis-resistant additive: leveling agent: color paste is added in a weight ratio of 100:300:15:1:1:1:20, and the mixed impregnation liquid is stirred at a stirring speed of 1000r / min at room temperature for 15-20 minutes until it is completely dissolved, and the viscosity is controlled at 140-200cps.
[0053] The configuration of the fabric includes: polyester polyether blended resin: dimethylformamide: non-ionic surfactant: hydrolysis-resistant additive: color paste: wood powder are added in a weight ratio of 100:40:1:0.5:2:3. The fabric is stirred at a high speed of 1500r / min at room temperature for 30-35 minutes until it is completely dissolved, stirred until the slurry is uniform, and the stirring speed is reduced to 300±50r / min for vacuum degassing for 90 minutes. The viscosity is controlled at 10000cps-12000cps (temperature 32°C).
[0054] (2) The coated surface layer enters a 30-meter-long three-fold solidification tank (water solidification length reaches 84 meters, solidification time is 7 minutes, and solidification speed is 12 meters / minute) for solidification. The solidification sugar content is 18-21% and the temperature is 30±2°C.
[0055] (3) After the synthetic leather semi-finished product comes out of the coagulation tank, the thickness is controlled between 1.35-1.40mm and the width is between 1.47-1.49m. Then it enters the washing tank (15 groups). The sugar content of the first six groups is controlled at 20-10%, the sugar content of the middle six groups is controlled at 10-0%, and the sugar content of the last three groups is 0%; the washing temperature of the last three groups is controlled at 70℃±5.
[0056] (4) After exiting the washing tank, the bass is pre-ironed by eight rounds of ironing rollers (temperature is 110±10℃); after pre-ironing, the bass is dried in an oven, and the oven temperatures are: 150℃ for the first group, 160℃ for the second to fourth groups, and 140℃ for the fifth group, until it is completely dried. After drying, the thickness of the roll is 1.1-1.2mm and the width is 145-147cm.
[0057] (5) The produced coffee grounds synthetic leather was tested for a three-centimeter peeling test, which reached 120N / 3cm; the softness value tested by a softness testing machine was between 2.0-2.5.
[0058] Example 2
[0059] (1) Use 0.85-0.95 mm non-woven fabric, first pass through the fabric storage rack, the speed is 10m / min, then pass through the impregnation tank with impregnation material, the pressure of the impregnation oil pressure roller is controlled at 5-5.5Kg. After impregnation, pass through the pre-coagulation liquid, the sugar content is 30-32%, the pressure of the pre-coagulation oil pressure roller is also controlled at 5-5.5Kg, then pass through the six-wheel ironing device (ironing temperature is controlled at 50 degrees Celsius), and finally pass through the coating table device equipped with a coating knife. At the same time, the fabric configured according to the following method is coated on the non-woven fabric along the scraper. The coating gap is controlled between 205±5 silk, and the coating amount is 1.3±0.05kg / y.
[0060] The configuration of the impregnation material includes: hydrolysis-resistant impregnation resin: dimethylformamide: tear-resistant additive: non-ionic surfactant: hydrolysis-resistant additive: leveling agent: color paste is added in a weight ratio of 100:380:15:1:1:1:20, and the mixed impregnation liquid is stirred at a stirring speed of 1000r / min at room temperature for 15-20 minutes until it is completely dissolved. Due to the use of thicker non-woven fabrics, the viscosity of the impregnation material is reduced by appropriately adjusting the number of dimethylformamide additions, and the viscosity is controlled at 80-120cps to ensure the overall feel.
[0061] The configuration of the fabric includes: polyester polyether blended resin: dimethylformamide: non-ionic surfactant: hydrolysis-resistant additive: color paste: wood powder are added in a weight ratio of 100:40:1:0.5:2:3. The fabric is stirred at a high speed of 1500r / min at room temperature for 30-35 minutes until it is completely dissolved, stirred until the slurry is uniform, and the stirring speed is reduced to 300±50r / min for vacuum degassing for 90 minutes. The viscosity is controlled at 10000cps-12000cps (temperature 32°C).
[0062] (2) The coated surface layer enters a 30-meter-long three-fold solidification tank (water solidification length reaches 84 meters, solidification time is 8.4 minutes, and solidification speed is 10 meters / minute) for solidification. The solidification sugar content is 18-21% and the temperature is 30±2°C.
[0063] (3) After the synthetic leather semi-finished product comes out of the coagulation tank, the thickness is controlled between 1.35-1.40mm and the width is between 1.47-1.49m. Then it enters the washing tank (15 groups). The sugar content of the first six groups is controlled at 20-10%, the sugar content of the middle six groups is controlled at 10-0%, and the sugar content of the last three groups is 0%; the washing temperature of the last three groups is controlled at 70℃±5.
[0064] (4) After exiting the washing tank, the bass is pre-ironed by eight rounds of ironing rollers (temperature is 110±10℃); after pre-ironing, the bass is dried in an oven, and the oven temperatures are: 150℃ for the first group, 160℃ for the second to fourth groups, and 140℃ for the fifth group, until it is completely dried. After drying, the thickness of the roll is 1.1-1.2mm and the width is 145-147cm.
[0065] (5) The produced coffee grounds synthetic leather was tested for a three-centimeter peeling test, and the result was 115N / 3cm. The softness test value was between 1.9-2.3.
[0066] Comparative Example
[0067] according to Figure 2 The process flow is carried out for production, and the process conditions are basically the same as those in Example 1, with the following differences: the resin is a polyester coating resin + a water repellent, and contains more fluoride; a single-layer coagulation tank is used for coagulation in water, the water coagulation length is 30 meters, the coagulation time is 2.5 minutes, and the coagulation speed is 12 meters / minute.
[0068] Figure 2 In the above-mentioned production process, the single layer solidifies at a fast solidification speed, resulting in coarse pores. The peeling data of three centimeters of stickers is 80N / 3cm. Although the coarse pore layer structure will improve the overall feel and air permeability, in order to ensure the peeling strength, the overall process formula is comprehensively considered and selected. Figure 1 The process conditions are more consistent with the expected test results.
[0069] By observing the cell layer structure with a magnifying glass, Example 1 has Figure 3 The blue pore structure shown has a relatively uniform pore distribution and a thin dense layer, which has a certain effect on air permeability.
[0070] From the above embodiments, it can be seen that the base fabric of the present invention is selected to contain recyclable coffee grounds short fiber components, and is matched with a fluorine-free resin with a suitable modulus. The pores of the PU coating are increased by adding wood powder and the like in the formula, so that the air permeability is better. The present invention adjusts the machine process, combines the wet process flow with the coffee carbon fiber base fabric, and the synthetic leather produced by the base fabric has good air permeability and good resilience. Moreover, the coffee yarn synthetic leather is environmentally friendly and has the characteristics of high adsorption and deodorization, which is conducive to application.
[0071] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for producing coffee yarn synthetic leather, characterized in that: The following steps are involved: A non-woven fabric containing coffee staple fibers is used as a substrate; the substrate components include coffee staple fibers, nylon and recycled polyester; the coffee staple fibers account for 15-20% of the substrate by weight; The substrate is sequentially subjected to impregnation rolling, pre-solidification, coating, and then solidified in water to obtain a semi-finished product; the impregnation material is fluorine-free and uses a hydrolysis-resistant impregnation resin; the coating process uses a polyester-polyether blended resin and adds wood powder; the weight ratio of the polyester-polyether blended resin to the wood powder in the slurry of the coating process is 100:1-5; The coagulated semi-finished product is washed with water, and then heated and dried to obtain coffee yarn synthetic leather.
2. The production method according to claim 1, characterized in that The impregnation material is obtained by stirring and mixing a hydrolysis-resistant impregnation resin and a first solvent; the room temperature viscosity of the impregnation material is controlled at 80-200 cps.
3. The production method according to claim 2, characterized in that: The slurry of the coating is fluorine-free and is obtained by stirring and mixing a polyester-polyether blended resin, wood powder and a second solvent; the mixed slurry is stirred at a stirring speed of 1000-1500 r / min for 30-35 minutes at room temperature.
4. The production method according to claim 3, characterized in that: The room temperature viscosity of the coating process slurry is 10000-12000 cps.
5. The production method according to claim 3, characterized in that: The first solvent and the second solvent are both dimethylformamide; color paste is added to the slurry of the impregnation material and the coating.
6. The production method according to any one of claims 1 to 5, characterized in that: The in-water coagulation adopts a three-layer coagulation method, and the feeding speed is 10-12m / min.
7. The production method according to claim 6, characterized in that: The thickness of the semi-finished product after solidification is controlled between 1.35-1.40 mm; the water washing is provided with multiple groups of water washing tanks, wherein the final water washing temperature is controlled at 60-80°C.
8. The production method according to claim 7, characterized in that: The heating and drying comprises: pre-ironing with an ironing roller at 100-120°C, and then drying at 140-160°C.
9. The coffee yarn synthetic leather obtained by the production method according to any one of claims 1 to 8 has a thickness of 1.1-1.2 mm and / or a softness test value of 1.9-2.5.
Citation Information
Patent Citations
Handball surface leather manufacturing method
CN106480746A
Fluorine-free anti-siphon high-density synthetic leather and production method thereof
CN111926579A